Validation of NHSN Annual Hospital Survey Questions: Do Responses Differ Depending on the Professional Completing the Survey?. (4th October 2017) - Kuper, Kristi; Van Santen, Katharina; Pakyz, Amy; Srinivasan, Arjun; O'Leary, Erin
Abstract: Background: Facilities enrolled in the National Healthcare Safety Network (NHSN) provide annual information on their antibiotic stewardship programs (ASPs) via a mandatory survey. The survey contains 12 questions that explore uptake of CDC's Core Elements for Hospital ASPs. Respondents (typically Infection Preventionists) are advised to seek input from pharmacist and physician ASP champions, but the professional completing the survey and the extent of input provided by ASP program personnel are unknown. A separate survey provided an opportunity to assess ASP responses reported to NHSN. Methods: Individuals from 446 academic and community hospitals participating in the Vizient list-serve were surveyed in March 2016. The Vizient survey included the 12 ASP questions in the 2015 NHSN survey. Vizient responses were compared with NHSN survey responses to assess differences in reported uptake of core elements based on the professional completing the survey. Results: 189 of the 211 hospitals completing the Vizient survey were successfully matched to NHSN hospitals. The majority of respondents were pharmacists; 83% were either Directors of Pharmacy or clinical pharmacists of which 48% and 61% reported assisting with the NHSN survey, respectively. Reported implementation of all 7 elements in this subset of 189 hospitals was 58.2% in the Vizient survey compared with 54.5% in NHSN. Results differed by respondent position and core element surveyed. Clinical pharmacists in the Vizient survey reported higher rates of core element adherence than Directors of Pharmacy (Figure 1). The position of survey respondents varied by hospital size. Of hospitals with less than 250 beds, 87.5% of surveys were completed by Directors of Pharmacy, whereas 77.1% of surveys were completed by clinical pharmacists in hospitals with ≥250 beds. Conclusion: Overall similarities between NHSN and Vizient survey results indicate that ASP questions based on CDC's Core Elements are interpreted in similar ways and answered consistently when analyzed overall. However, individual core element responses may differ based on position of respondent, ASP familiarity, ASP infrastructure, and/or hospital bed size. CDC is exploring improved wording of the survey questions to help further improve consistency in responses. Disclosures: All authors: No reported disclosures.